Frequency of influenza H3N2 intra-subtype reassortment: attributes and implications of reassortant spread. Issue 1 (December 2016) - Maljkovic Berry, Irina; Melendrez, Melanie; Li, Tao; Hawksworth, Anthony; Brice, Gary; Blair, Patrick; Halsey, Eric; Williams, Maya; Fernandez, Stefan; Yoon, In-Kyu; Edwards, Leslie; Kuschner, Robert; et al.
Abstract Background Increasing evidence suggests that influenza reassortment not only contributes to the emergence of new human pandemics but also plays an important role in seasonal influenza epidemics, disease severity, evolution, and vaccine efficacy. We studied this process within 2091 H3N2 full genomes utilizing a combination of the latest reassortment detection tools and more conventional phylogenetic analyses. Results We found that the amount of H3N2 intra-subtype reassortment depended on the number of sampled genomes, occurred with a steady frequency of 3.35%, and was not affected by the geographical origins, evolutionary patterns, or previous reassortment history of the virus. We identified both single reassortant genomes and reassortant clades, each clade representing one reassortment event followed by successful spread of the reassorted variant in the human population. It was this spread that was mainly responsible for the observed high presence of H3N2 intra-subtype reassortant genomes. The successfully spread variants were generally sampled within one year of their formation, highlighting the risk of their rapid spread but also presenting an opportunity for their rapid detection. Simultaneous spread of several different reassortant lineages was observed, and despite their limited average lifetime, second and third generation reassortment was detected, as well as reassortment between viruses belonging to different vaccine-associated clades, likely displaying differing antigenic properties. Some of the spreading reassortants remained confined to certain geographical regions, while others, sharing common properties in amino acid positions of the HA, NA, and PB2 segments, were found throughout the world. Conclusions Detailed surveillance of seasonal influenza reassortment patterns and variant properties may provide unique information needed for prediction of spread and construction of future influenza vaccines.